Identification of cuproptosis-associated IncRNAs signature and establishment of a novel nomogram for prognosis of stomach adenocarcinoma - Yu, Wei; Huo, Hongqi; You, Zhixin; Lu, Rong; Yao, Tianci; Huang, Jing (Frontiers in Genetics, 2022)
Purpose: Stomach adenocarcinoma (STAD) is still common globally. Cuproptosis is a newly identified cell death pattern. The role of cuproptosis-associated lncRNAs in STAD is unknown. Methods: STAD patient data from TCGA were used to identify prognostic lncRNAs by Cox regression and LASSO. A nomogram was constructed to predict patient survival. The biological profiles were evaluated through GO and KEGG. Results: We identified 298 cuproptosis-related lncRNAs and survival-related 13 lncRNAs (P < 0.05). Patients could be categorized into either high risk group or low risk group with 9- lncRNAs risk model, with significantly different survival time (P<0.001). ROC curve and nomogram confirmed the 9-lncRNA risk mode had good prediction capability. Patients in the lower risk score had high mutation burden. We also found that patients in the two groups might respond differently to immune checkpoint inhibitors and some anti-tumor compounds. Conclusion: The nomogram with 9-lncRNAs may help guide treatment of STAD. Future clinical trials are necessary to verify the nomogram.